Extended Family, Neighbourhood and Friends’ Network in Supporting Caregivers of Older People with Mental Health Problems (Jurnal Pembangunan Sosial, 2013)
Caregivers of older people with mental health problems encountered with minimal support and assistance in their caregiving responsibility. Despite all the positive and negative experiences faced by the caregivers, the family network, network of friends and some local informal networks supported their roles although there were contested beliefs between traditional, religious and modern perspectives. The article will be addressed the different help and support provided by the extended family, neighbourhood support, neighbours and friends’ network. Caregivers address the need for appropriate support and resources to help them in managing and providing ‘good quality care’ to their mentally ill family member.